Muslim international students in the U.S.: a phenomenological inquiry into the experience of identities - Anderson, Donna L., author; Kuk, Linda, advisor; Archie, Tiffenia, committee member; Muñoz, Susana, committee member; Tungate, Susan, committee member (Colorado State University. Libraries, 2019)
The number of Muslim international students in the U.S. has grown considerably in recent years, however these students face unique challenges related to their religious, racial/ethnic, and gender identities. By better understanding how Muslim international students experience their identities on U.S. campuses, university practitioners can better meet the unique needs of Muslim international students and assist them in succeeding and graduating. The purpose of this qualitative phenomenological study was to better understand how Muslim international students experience their identities at four-year universities in the Midwestern U.S. using Kim's (2012) International Student Identity (ISI) model as a guiding framework. Specifically, the study explored how Muslim international students experience their religious, ethnic/racial, and gender identities prior to coming to the U.S. and as students in the Midwestern U.S. This phenomenological study included semi-structured interviews with ten students who attended four-year institutions in the Midwestern U.S. Significant findings in this study emerged from six themes and included: (1) difficulties in practicing Islamic prayer in the Midwestern U.S., (2) Islam as a flexible religion, (3) racial construct as a new and troubling concept, (4) male/female interactions on campus and in the classroom, (5) perceptions of veiling in the Midwestern U.S., (6) stereotypes of Muslim international students based upon their national identity, (7) fear of practicing Islamic prayer due to stereotypes of Muslims, (8) coping with acts of discrimination, and (9) impact of Trump administration rhetoric and policies. Emergent themes in this study were viewed through Kim's (2012) International Student Identity model.
Keywords: international student identity model; Muslim; international students; identity; phenomenology; Trump